Data binding with Windows Forms 2.0 : programming smart client data applications with .NET - Noyes, Brian (Microsoft .NET development series., 2006)
"Brian Noyes' writing style easily captures your attention as he elaborates on all aspects of data binding in his book. He has a refreshingly clear and crisp delivery as he starts each chapter with a simple tour of each topic, and then leads you into practical concerns for sound practices and extensibility opportunities. Most importantly, as Brian explains approaches to data-binding architecture, patterns of usage, the value of data sets, binding controls and the rest, he always describes how he reaches his recommendations on the topic. This book is perfect for newcomers to .NET 2.0, but also for those that have some experience. Anyone who cares about data in their applications (okay, that should be almost everyone) is guaranteed to learn something new and useful by reading Brian's book." -Michele Leroux Bustamante, IDesign chief architect, Microsoft regional director, and MVP "Brian has saved me a lot of time. I'm writing The Hitchhiker's Guide to Visual Studio and SQL Server 2005 (7th Edition) and I'm not going to have to cover data binding nearly as deeply because Brian has done it for me. His book gets right to the meat of the subject and makes data binding look easy. I was also pleased to see that the book focuses on the misunderstood and under-applied Windows Forms architecture. It's a must-read for anyone trying to make their application more interactive and to leverage the new Visual Studio 2005 technology. I'm planning to point my readers to this resource when they need an in-depth treatment of data binding." -William Vaughn, president, Beta V Corporation "Data binding has finally come of age in Windows applications. Back in the Visual Studio 6.0 days, I ignored data binding completely and wrote my own repetitive code to encapsulate my business logic. With Visual Studio 2005, we finally have a robust and compelling data-binding technology. To ignore it today would make you inefficient and put you behind the curve. Brian delivers a clear and concise discussion of a core topic of development for Windows today. A combination of an easy-to-follow conversational yet technical tone, excellent examples, and solid explanations make this a must-read for any developer writing for Windows or learning to write for Windows." -Stephen Forte, chief technical officer, Corzen Inc. "This book provides a clear, readable, and in-depth treatment of data binding, with detailed discussions of best practices in the presentation and use of data. Brian c...